HIGH DIETARY FRUCTOSE DOES NOT EXACERBATE THE DETRIMENTAL CONSEQUENCES OF HIGH FAT DIET ON BASILAR ARTERY FUNCTION - (:unkn) unknown (POLISH PHYSIOLOGICAL SOC, 2016)
The objective of the study was to determine the effects of a high fat (HF) diet alone or with high fructose (HF/F) on functional and structural changes in the basilar arteries and cardiovascular health parameters in rats. Male Sprague Dawley rats were fed either a HF (30%) or HF/F (30/40%) diet for 12 weeks. The basilar artery was cannulated in a pressurized system (90 cm H2O) and vascular responses to KCl (30 - 120 mM), endothelin (10(-11) - 10(-7) M), acetylcholine (ACh) (10(-10) - 10(-4) M), diethylamine (DEA)-NONO-ate (10(-10) - 10(-4) M), and papaverine (10(-10) - 10(-4) M) were evaluated. Rats were also monitored for food intake, body weight, blood lipids, blood pressure, and heart rate. At death, asymmetrical dimethyl arginine level (ADMA) and leptin were assayed in serum. Although there was no significant difference in weight gain and food intake, HF and HF/F diets increased body fat composition and decreased the lean mass. HF/F diet accelerated the development of dyslipidemia. Although resting blood pressure remained unchanged, stress caused a significant elevation in blood pressure and a modest increase in heart rate in HF fed rats. Both HF and HF/F diet resulted in decreased response to endothelium-dependent and - independent relaxation, whereas increased basilar artery wall thickness was observed only in HF group. Serum leptin levels positively correlated with wall thickness. Moreover serum ADMA was increased and eNOS immunofluorescence was significantly decreased with both diets. These data suggest that the presence of high fructose in a HF diet does not exacerbate the detrimental consequences of a HF diet on basilar artery function.
Keywords: basilar artery; cerebrovascular; high fat; fructose; diet; nitric oxide; endothelin-1; endothelium; contractility; relaxation; asymmetrical dimethyl arginine level; leptin; papaverine; acetylcholine; heart; blood pressure; oxidative; obesity; CEREBRAL-BLOOD-FLOW; CARDIOVASCULAR-SYSTEM; VASCULAR DYSFUNCTION; OXIDATIVE STRESS; LEPTIN; OBESITY; RATS; AGE; EXPRESSION; REVERSAL